`(3x^(-2)+(2x-1)^(-1))/(6/(x^-1+2)+3x^-1)` Simplify the complex fraction.

Expert Answers

An illustration of the letter 'A' in a speech bubbles

`(3x^(-2)+(2x-1)^(-1))/(6/(x^(-1)+2)+3x^(-1))`

First, apply the negative exponent rule `a^(-m)=1/a^m` .

`=(3/x^2+ 1/(2x-1))/(6/(1/x+2) + 3/x)`

Then, simplify the fraction `6/(1/x+2)` . To do so, multiply it by `x/x` .

`=(3/x^2+ 1/(2x-1))/(6/(1/x+2) *x/x+ 3/x)`

`=(3/x^2+ 1/(2x-1))/((6x)/(1+2x) + 3/x)`

`=(3/x^2+ 1/(2x-1))/((6x)/(2x+1) + 3/x)`

Then, multiply the top and bottom of the complex fraction by the LCD of the four fractions present.  The LCD is `x^2(2x - 1)(2x + 1)` .

`=(3/x^2+ 1/(2x-1))/((6x)/(2x+1) + 3/x)*(x^2(2x-1)(2x+1))/(x^2(2x-1)(2x+1))`

`=(3(2x-1)(2x+1) + x^2(2x+1))/(6x(x^2)(2x-1)+3x(2x-1)(2x+1))`

To simplify it further, factor out the GCF in the numerator. Also, factor out the GCF of the denominator.

`= ((2x+1)(3(2x-1) + x^2))/(3x(2x-1)(2x^2+2x+1))`

`=((2x+1)(6x-3+x^2))/(3x(2x-1)(2x^2+2x+1))`

`= ((2x+1)(x^2+6x-3))/(3x(2x-1)(2x^2+2x+1))`

Both numerator and denominator are now in factored form. Since there is no common factor between them, no factors are cancelled.

Therefore, the simplified form is

 `(3x^(-2)+(2x-1)^(-1))/(6/(x^(-1)+2)+3x^(-1))= ((2x+1)(x^2+6x-3))/(3x(2x-1)(2x^2+2x+1))` .

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial